Association between regional tau pathology and neuropsychiatric symptoms in aging and dementia due to Alzheimer's disease - Tissot, Cécile; Therriault, Joseph; Pascoal, Tharick A.; Chamoun, Mira; Lussier, Firoza Z.; Savard, Melissa; Mathotaarachchi, Sulantha S.; L. Benedet, Andréa; Thomas, Emilie M.; Parsons, Marlee; Nasreddine, Ziad; Rosa‐Neto, Pedro; et al. (Alzheimer's & dementia : translational research & clinical interventions, 2021)
Background Neuropsychiatric symptoms (NPS) are frequent in aging and Alzheimer's disease (AD). Here we study the relationship between NPS and AD pathologies in vivo. Method Two hundred and twenty‐one individuals from the TRIAD cohort (143 cognitively unimpaired, 52 mild cognitive impairment, and 26 AD) underwent [18F]MK6240‐tau‐positron emission tomography (PET), [18F]AZD4694‐amyloid‐PET, magnetic resonance imaging, and neuropsychological evaluations. Spearman correlations and voxel‐based regression models evaluated the relationship between Neuropsychiatric Inventory Questionnaire (NPI‐Q) scores, and tau‐PET, amyloid‐PET, and voxel‐based morphometry. Results Fifty percent of individuals presented NPS; these correlated with tau, not amyloid beta or neurodegeneration. Associations between NPI‐Q score and tau‐PET were stronger in the parietal association area, superior frontal, temporal, and medial occipital lobes. NPI‐Q domains associated with distinct patterns of tau uptake. Conclusions NPS are predominantly related to tau in aging and dementia. Regions affected are part of the behavioral circuits, and vulnerable to early AD pathology. Domain‐specific analyses showed NPS are related to the AD pathophysiological processes in a symptom‐specific manner.